Retraction notice to:A study approach on ferroelectric domains in BaTiO3 [Mater. Charact. 120C (2016) 257–262] - Rocha, L. S.R. [UNESP]; Cavalcanti, C. S. [UNESP]; Amoresi, R. A.C. [UNESP]; Stojanovic, B. D.; Borsari, E. [UNESP]; Zaghete, M. A. [UNESP]; Simões, A. Z. [UNESP] (Elsevier, 2019)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal). This article has been retracted at the request of Authors. The results presented in this paper have been copied from the paper “Imaging of nanometric domains in BaTiO3 using AFAM and PFM” Mangamma, G.; Ramachandran, B.; Sairam, T. N.; Rao, M. S. R.; Dash, S.; Tyagi, A. K., Journal of Advanced Microscopy Research, Volume 6, Number 1, February 2011, pp. 29-34(6). A member of the group of authors who helped to collect the data for the paper passed away prior to the paper being finalised, and the remaining authors on the paper failed to check the validity and originality of the results prior to submitting the paper to the journal. All authors involved in the referred paper humbly apologize to the readers, referees and editors of Materials Characterization, and especially to the authors of the paper from which the results have been copied.